USULAN PERBAIKAN KUALITAS PRODUK KAYU MANIS DI INDUSTRI REMPAH-REMPAH DENGAN METODE DMAIC - Winda Purwani (Universitas Mercu Buana, 2015)
Abstract. The research aimed to find out the cause of reject and found theproposed improvements in order to reduce the number of reject broken and cleancinnamon product. By using the approach of DMAIC method to identify theproblem by using SIPOC diagram to explain the existing processes as well as datacollection through sources and related documents. Known to the average speed ofthe input material and finding foreign objects into the main cause of reject brokenand clean cinnamon product. Measurement of process capability using Minitab16.0 software for speed of the input material and foreign material separation. Rootcause of the problem is analyzed using a fishbone diagram. Found cause of rejectthat dirty material, material feeding is not appropriate, no maximum enginecapacity, setting of suction at Tarara machines and the absence of a standardreference in the suction. Repairs to the causes of the problem were analyzed using5W1H table. Results fixes known increase the average speed of the input materialin the automation line and reduce the number of foreign material finding whichdecrease the number of reject broken and clean cinnamon products. Someproposed improvements to reduce reject: supplier performance monitoring byvisiting the land, audits, and training, prohibit the use of plastic bags as packagingand the wood pallet as material storage, conduct supplier performance evaluation,make improvements to the production machine, the setting of the suction machineTarara, and set the standard suction reference.Keyword: DMAIC, Reject, SIPOC, Fishbone Diagram, Cinnamon